Retinol‐binding protein 4 levels and susceptibility to ischaemic events in men. (11th January 2014) - Cubedo, Judit; Padró, Teresa; Cinca, Juan; Mata, Pedro; Alonso, Rodrigo; Badimon, Lina
Abstract Background Many efforts in cardiovascular medicine have been focused in the identification of patients at risk of developing an acute ischaemic event. Biomarker discovery studies have become an essential research area, being proteomic technologies an excellent tool for biomarker identification. By applying proteomic approaches, we have detected changes in retinol‐binding protein 4 (RBP4) in acute new‐onset myocardial infarction patients (AMI) and in high‐risk patients with heterozygous familial hypercholesterolaemia (FH). Materials and methods Differential serum proteome was analysed by two‐dimensional electrophoresis and MALDI‐TOF/TOF. Validation studies were performed by ELISA, and functional effects of RBP4 were tested in cell culture experiments. Results Retinol‐binding protein 4 proteomic characterization depicted two spots (pI = 5·4;Mw = 23·01/22·78 kDa) with decreased intensity in AMI patients. Total serum RBP4 levels were decreased in AMI patients (N = 68) compared with controls (N = 132; P < 0·0001). RBP4 was also decreased in FH patients who had an ischaemic event 2 years (±0·3) after their inclusion compared with FH patients without any cardiovascular episode at follow‐up (P < 0·001; N = 187). In both cases, changes were limited to men. RBP4 induced a significant increase in eNOS expression in human endothelial vascular cells and in prostaglandin I2 release in coronary vascular smooth muscle cells. Conclusions We show decreased serum RBP4 levels in men in the acute phase of AMI, being this decrease already detected in men with FH previous to the presentation of an ischaemic event. The decrease in RBP4 levels could confer an increased susceptibility to the precipitation of an ischaemic event that could be mediated by the decrease in its vasculoprotective properties through NO and PGI2.